Institutionalising Peace Education in Pesantren: Pedagogical and Institutional Pathways To Anti-Violence Character Formation - Sabiq, Zamzami; Takdir, Mohammad (el-Tarbawi, 2026)
This study investigates how peace education is institutionalised within the pedagogical and organisational practices of an Islamic boarding school (pesantren) to foster anti-violence character formation among students. Using a qualitative case study, data were collected from 8 participants selected through purposive sampling, including kiai, teachers, students, administrators, and alumni, through semi-structured interviews, participant observation, and document analysis. The findings reveal three key patterns. First, peace education is embedded in everyday religious learning and character-based pedagogy grounded in the values of prophecy, compassion, respect, and moral responsibility. Second, institutional mechanisms—including mediation practices, counselling, ta’zir (educational disciplinary measures), and curriculum integration—reinforce the internalisation of non-violent values. Third, the leadership of the kiai, together with community and family engagement, strengthens the sustainability of peace education beyond the classroom. This study advances peace education scholarship by proposing an institutional model of peace education in pesantren, demonstrating how religious pedagogy and institutional culture operate together to cultivate anti-violence character within an Islamic educational setting